COLONIES IN THE HISTORICAL AND POLITICAL PERSPECTIVE: THE ATTEMPT OF SYSTEMATIZATION - Баталов, О. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
In the article, through the comparative analysis of the colonies in the historical and politicalperspective, the features of the colony were singled out and the new definition of the colony wasformulated and the author's colonies typology was proposed. It reaches the conclusion that the proposedtypology of colonies provides new opportunities for analysis of modern postcolonial societies and states.